ANALISIS AERODINAMIS SECARA TEORITIS DAN PENERAPAN APLIKASI INVENTOR DAN CFD PADA RANCANG BANGUN PROTOTYPE MOBIL LISTRIK “INKAS A6” BLDC 1000 WATT DENGAN KONSEP SHUTTLE GOLF - Jamaludin, Jamaludin; Efrizal, Efrizal; Ardian, M Arief Alfi; Hendrajit, Deco (Universitas Muhammadiyah Tangerang, 2024)
The more rapid development of the times in the era of globalization and technology, the use of transportation is the best solution to support increased human mobility. It is noted that the use of land transportation has increased along with the increase in human mobility. This matter was also followed by the existence of global issues regarding the energy crisis that hit the world. The need for transportation is increasing, resulting in an increase in the energy required.This final project report entitled